Characterization of long‐term in vitro culture‐related alterations of human tonsil‐derived mesenchymal stem cells: role for CCN1 in replicative senescence‐associated increase in osteogenic differentiation. Issue 5 (23rd August 2014) - Yu, Yeonsil; Park, Yoon Shin; Kim, Han Su; Kim, Ha Yeong; Jin, Yoon Mi; Jung, Sung‐Chul; Ryu, Kyung‐Ha; Jo, Inho
Abstract Although mesenchymal stem cells (MSC) isolated from bone marrow and adipose tissues are known to be subjected to in vitro culture‐related alterations in their stem cell properties, such data have not been reported in human tonsil‐derived MSC (T‐MSC). Here, we investigated the culture‐related changes of phenotypes, the senescence, and the differentiation potential of T‐MSC. T‐MSC were serially passaged by a standard protocol, and their characteristics were assessed, including MSC‐specific surface antigen profiles, the senescence, and the differentiation potentials into adipocytes, chondrocytes and osteocytes. Up to at least passage 15, we found no alterations in either MSC‐specific surface marker, CD14, CD34, CD45, CD73 and CD90, or the mRNA expression of embryonic stem cell gene markers, Nanog, Oct4‐A and Sox‐2. However, the expression of CD146, recently identified another MSC marker, dramatically decreased with increasing passages from 23% at passage 3 to 1% at passage 15. The average doubling time increased significantly from 38 h at passage 10 to 46 h at passage 15. From passage 10, the cell size increased slightly and SA‐β‐gal staining was evident. Both Alizarin Red S staining and osteocalcin expression showed that the osteogenic differentiation potential increased up to passage 10 and decreased thereafter. However, the adipogenic and chondrogenic differentiation potential decreased passage‐dependently from the start, as evidenced by staining of Oil Red O and Alcian Blue, respectively. Consistent with a passage‐dependent osteogenic differentiation, the expression of CCN1, an angiogenic protein known to be related to both senescence and osteogenesis, also increased up to passage 10. Furthermore, ectopic expression of small interfering RNA against CCN1 at passage 10 significantly reversed Alizarin Red S staining and osteocalcin expression. Altogether, our study demonstrates the characterization of long‐term in vitro cultured T‐MSC and that CCN1 may be involved in mediating a passage‐dependent increase in osteogenic potential of T‐MSC.